2020
DOI: 10.1002/app.50207
|View full text |Cite
|
Sign up to set email alerts
|

Mixed substituent ether‐containing polyphosphazene/poly(bis‐phenoxyphosphazene) blends as membranes for CO2 separation from N2

Abstract: Polyphosphazenes gain much of their physical and chemical properties from the substituents attached to the phosphorus atoms in the backbone. Poly(phosphazenes) that have short‐chain polyether containing substituents, such as, 2‐(2‐methoxyethoxy)ethanol, have high CO2 permeability and selectivity over N2 as well as resistance to degradation under humidification at 60°C. However, the principal shortcomings of this polymer are the poor mechanical and surface characteristics. Blending of an example of this polypho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In this study, we utilized seven polymer backbone structures, as recommended by our experimental colleagues, and these structures are illustrated in Figure . Polymer backbones that have demonstrated good performance in producing rubbery polymer membranes for gas separation applications were targeted. Rubbery polymers deliver stable and durable gas separation performance compared to their counterparts– glassy polymers that usually experience physical aging.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we utilized seven polymer backbone structures, as recommended by our experimental colleagues, and these structures are illustrated in Figure . Polymer backbones that have demonstrated good performance in producing rubbery polymer membranes for gas separation applications were targeted. Rubbery polymers deliver stable and durable gas separation performance compared to their counterparts– glassy polymers that usually experience physical aging.…”
Section: Methodsmentioning
confidence: 99%
“…All the backbones examined in this study have demonstrated good performance in producing polymer membranes. [46][47][48][49][50][51][52]…”
Section: Polymer Backbones Usedmentioning
confidence: 99%
“…Our research group has developed membranes that can enrich CO 2 concentration from low carbon emitting sources using the concept of low-concentration CO 2 enrichment [47]. Over the course of last three decades, several unique polyphosphazenes have been developed for a variety of applications [43][44][45][46][48][49][50][51][52][53][54][55][56][57][58]. Among these polyphosphazenes, poly[bis((2-methoxyethoxy)ethoxy) phosphazene (MEEP, Figure 1) is a specialty polymer that can fabricate thin, self-healing CO 2 /N 2 selective membranes [59].…”
Section: Introductionmentioning
confidence: 99%